Hole blocking in carbon nanotube-polymer composite organic light-emitting diodes based on poly (m-phenylene vinylene-co-2, 5-dioctoxy-p-phenylene vinylene) - BLAU, WERNER (My University, 2000)
In order to investigate the role of carbon nanotubes in a polymer matrix, organic light-emitting diodes were fabricated from a polymer composite composed of poly ~ m -phenylene vinylene-co-2,5-dioctoxy- p -phenylene !~ PmPV ! and dispersed single-wall carbon nanotubes ~ SWNTs ! . Tris- ~ 8-hydroxyquinolinolato ! aluminum (Alq 3 ) doped by Nile Red was used as an emissive material between the polymer composite and cathode. The device fabricated without SWNTs dispersed in the PmPV shows a dominant emission near red at 600 nm, which is in the range of the characteristic emission of Nile Red-doped Alq 3 , with a small amount of green emission from the PmPV. However, the devices fabricated with the polymer composite show an increase in the oscillator strength of the green emission with a dominant emission peak near 500 nm, the characteristic emission of PmPV. This was observed for SWNT concentrations up to 0.1 wt %. The shift in the emission indicates that the SWNTs in the PmPV matrix act as a hole-blocking material that results in a shifting of the recombination region from the Nile Red-doped Alq 3 layer to the PmPV composite layer.
PUBLISHED
Keywords: SWNT; SWNT